2013
DOI: 10.1155/2013/654645
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Hyperalgesia in Pigs through Blocking Low Hydraulic Resistance Channels and Reduction of the Resistance through Acupuncture: A Mechanism of Action of Acupuncture

Abstract: According to the classic theory of Chinese medicine, pain is due to the blockage in meridian channels, and acupuncture was invented to treat pain by “dredging” the channels. To test the theory, a hyperalgesia model was made by injecting hydrogel into low hydraulic resistance channel (LHRC) in 12 anaesthetized minipigs. Tail-flick threshold and ear-flick threshold were measured using a thermal radiation dolorimeter, and relative flick threshold (RFT) was calculated. Hydraulic resistance (HR) was measured with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Injecting gel into these channels effectively blocked the signals transmitted through them and allows us to create a pathological model of channel stasis in mini-pigs [3]. Further research showed that blocking these pathways with gel lowered the pain threshold along the meridians after a certain time had elapsed, thus corroborating the principle of "when there is blockage there is pain" that is fundamental in Chinese medical theory [4]. Another study showed that blocking LHRC along the stomach meridian in mini-pigs causes pathological changes such as bloating in the stomach and intestines that are classically attributed to pathology of the stomach meridian and stomach-fu.…”
Section: Introductionmentioning
confidence: 87%
“…Injecting gel into these channels effectively blocked the signals transmitted through them and allows us to create a pathological model of channel stasis in mini-pigs [3]. Further research showed that blocking these pathways with gel lowered the pain threshold along the meridians after a certain time had elapsed, thus corroborating the principle of "when there is blockage there is pain" that is fundamental in Chinese medical theory [4]. Another study showed that blocking LHRC along the stomach meridian in mini-pigs causes pathological changes such as bloating in the stomach and intestines that are classically attributed to pathology of the stomach meridian and stomach-fu.…”
Section: Introductionmentioning
confidence: 87%
“…结论: 本研究对小型猪四肢间质通道的系统观察, 揭示了生物体中存在的一种新结构, 其分布和数目与人 体十二经脉相同, 与《黄帝内经》"卫在脉外""伏行于分肉之间""如雾露之溉"等描述相吻合 [63] . 针刺可 使间质通道的流阻降低 [64] , 荧光素钠迁移轨迹变长变宽 [65] ;堵塞循经间质通道可引起痛阈降低(经络"不通则 痛") [64] 、 相关脏器失常 [66,35,36] 、经脉病候 [34] 和病理学变化 [67] . 间质通道的存在还可解释经络的低流阻、低阻 抗和高导声等生物物理学特性 [68] , 结合所依托的筋膜组织, 可解释经络的高振动声特性 [69] , 结合神经轴突反 射和间质中的容积传输, 可解释循经感传现象 [58] .…”
Section: 循经间质组织液通道的生理学意义与人体经络功能的比较unclassified
“…The ISF only flows under conditions of low hydraulic resistance. Blockage of these channels in pigs induces hyperalgesia [139]. Release of tight tissues, following myoActivation, may help to restore interstitial fluid flow and promote the delivery of nutrients and removal of metabolic waste of surrounding tissues.…”
Section: The Interstitial Spacementioning
confidence: 99%